Treatment of Recurrent Aphthous Ulcers in an HIV Patient – An Emerging Use for Pentoxifylline - Kathryn Lynn Slayter; Thomas J Marrie (Canadian Journal of Infectious Diseases)
Patients with human immunodeficiency virus (HIV) infection often suffer from persistent, painful ulcers that commonly occur on the soft palate, buccal mucosa, tonsillar area or tongue, which are referred to as aphthous ulcers. This paper reports the case in which pentoxifylline was successfully used to treat recurrent aphthous ulcers in an HIV patient.